PENGEMBANGAN PRODUK KERUPUK UDANG MELALUI SUBSTITUSI TEPUNG UBI JALAR UNGU (Ipomoea batatas Lam)DENGAN VARIASI LAMA PENGGORENGAN - Andi Anindita Rahmayani; Kadirman Kadirman; Muhammad Wiharto Caronge (Universitas Negeri Makassar, 2016)
The aims of this research to determine the effect of purple sweet potato flour, frying time, and to determine the level of acceptance sensoric analysis. This research was conducted in two steps: the first consisting of a sensory attributes and hedonic test. The second step is conducting chemical analysis (water content, protein content, and total anthocyanin). The experimental design using Completely Randomized Design pattern Factorial (CRD Factorial) consisting of two factors: the concentration of the addition of sweet potato flour purple with three levels of treatment are: 5%, 10%, and 15% and the time frying are: 10 seconds, 15 seconds, and 20 seconds. The resultsof sensory attributes and hedonic test showed that the best treatment is the substitution of 5% and 10% purple sweet potato flour respectively at the time of frying 10 seconds and 15 seconds. The results of chemical analysis are water content (1.52%), protein content (7.16%), and the total anthocyanins (0.03%) at 5% purple sweet potato flour an 10 seconds time of frying